Menafsirkan Film Horor Supranatural dengan Wawasan Dunia Kristen - Hendra Winarjo (Sekolah Tinggi Teologi Baptis Indonesia, 2022)
This article offers a theological framework for interpreting supernatural horror films with a Christian worldview based on narratives of creation, fall, redemption, and glorification. By doing library research, this article describes supernatural horror films. It analyzes a Christian worldview of the relationship between God, humans, and demons, as well as the pocong film through that worldview. Thus, supernatural horror films can show values and hopes that support Christian narratives. On the other hand, it can also reject Christian narratives because supernatural horror films as religious and cultural products have values and ideas that are not always in line with God's revelation, which is rooted in God's revelation that views demons and so on as finite creation, has been defeated through the work of Christ, and the promise of demons final defeat and so on in the new heaven and earth. Ultimately, this article interprets the pocong film narrative as a case study. As a result, pocong films have a discrepancy with Christian narratives, such as the dead being able to